Design diagrams for wavelength discrepancy in tank testing with inconsistently scaled intermediate water depth. (June 2017) - Noble, Donald R.; Draycott, Samuel; Davey, Thomas A.D.; Bruce, Tom
Highlights: Wave parameter errors described for tank tests with inconsistently scaled water depth. Potential errors include wavelength, steepness, celerity, group velocity, and power. Design diagrams are presented to quantify and visualise these discrepancies. This will facilitate experimental planning, particularly in intermediate depth water. Abstract: The well-known dispersion relation links the length and period of a water wave with the depth in which it propagates. When model testing in tanks, the water depth should be consistently scaled to correctly replicate the waves. While this is done routinely by scaling foreshore bathymetry in coastal engineering physical model studies, and is not significant for deep water scenarios, this is not always considered when testing marine renewable energy devices, which are often in intermediate depth. Where water depth is not scaled consistently there will be resulting errors in wave parameters including wavelength, steepness, celerity, group velocity, and power. Design diagrams are presented to quantify and visualise these discrepancies over a typical range for testing offshore renewable energy devices. This design tool will facilitate experimental planning, quantification of uncertainties, and correlation of model test results with field data.